A dietary polysaccharide from Eucheuma cottonii downregulates proinflammatory cytokines and ameliorates osteoarthritis-associated cartilage degradation in obese rats. Issue 9 (22nd August 2019) - Sudirman, Sabri; Chang, Heng-Wei; Chen, Chun-Kai; Kong, Zwe-Ling
Abstract : A dietary polysaccharide extracted from Eucheuma cottonii downregulated proinflammatory cytokines and cartilage degradation enzymes as well as suppressed cartilage degradation. Abstract : Osteoarthritis (OA) is a common form of arthritis, which is characterized by the degeneration of articular cartilage, leading to joint dysfunction. Oral drug therapy seems to ameliorate some signs and symptoms of OA, but may be accompanied by side effects and does not appear to be effective long-term. Seaweed has received much attention for pharmacological application due to its various biomedical properties, including the anti-inflammation, antitumor, and antioxidant effects. This study investigated the ameliorative effects of a dietary polysaccharide from Eucheuma cottonii extract (ECE) on an anterior cruciate ligament transection with partial medial meniscectomy surgery (ACLT+MMx) to induce OA in high-fat diet (HFD)-induced obese rats. Male Sprague-Dawley rats were fed an HFD for 12 weeks before ACLT+MMx surgery, after which they were administered a daily oral gavage of saline (Sham, OB Sham, and OBOA) and either low-dose ECE (100 mg per kg body weight), high-dose ECE (400 mg per kg body weight), or glucosamine sulfate as a positive control (OBOAGS; 200 mg per kg body weight) for 5 weeks. Treatment with ECE decreased the body weight, triglyceride and total cholesterol (TC) levels, and the TC/high-density lipoprotein (HDL)-C ratio in the obese rats. Additionally, ECE downregulated the expression of proinflammatory cytokines, including tumor necrosis factor-α, interleukin-1β, and leptin, and suppressed nuclear factor-kappa B and extracellular-signal-regulated kinase-1/2 expression, resulting in a decrease in the levels of matrix metalloproteinase (MMP)-1 and MMP-13 and prostaglandin-E2 and attenuated cartilage degradation. These results demonstrate that the dietary polysaccharide from ECE can suppress OA development in obese rats, suggesting its potential efficacy as a promising candidate for OA treatment.